Old age from Antiquity to post-modernity - Johnson, Paul (Paul A.); Thane, Pat (Routledge studies in cultural history., 1998)
Featuring both methodological and empirical studies, Old Age represents a substantial contribution to the historical understanding of old age in past societies, as well as to the debate about post-modernism in historical study.